Natural polymers aposites for skin regeneration - Olivas-Armendariz, I.; Valencia-Gómez, L E.; Martel-Estrada, S. A.; Vargas-Requena, C. L.; Rodriguez-González, C. A. (Revista Mexicana de Ingenieria Biomedica, 2016)
This review includes the bio-polymers most used in recent years for the manufacturing of materials used as dressings in cutaneous wound healing and skin regeneration. Also, the natural polymers most studied in tissue engineering are mentioned, highlighting their physical, chemical and biological properties for skin regeneration and wound healing. Through an extensive review of the clinical and research uses different types of natural polymers were compared, as well as the results of chemical and biological tests carried out during experimental research performed internationally.